Isosteric replacements of the carboxylic acid of drug candidate VX-787: Effect of charge on antiviral potency and kinase activity of azaindole-based influenza PB2 inhibitors. Issue 9 (1st May 2015) - Boyd, Michael J.; Bandarage, Upul K.; Bennett, Hamilton; Byrn, Randal R.; Davies, Ioana; Gu, Wenxin; Jacobs, Marc; Ledeboer, Mark W.; Ledford, Brian; Leeman, Joshua R.; Perola, Emanuele; Wang, Tiansheng; et al.
Graphical abstract: Abstract: VX-787 is a first in class, orally bioavailable compound that offers unparalleled potential for the treatment of pandemic and seasonal influenza. As a part of our routine SAR exploration, carboxylic acid isosteres of VX-787 were prepared and tested against influenza A. It was found that the negative charge is important for maintaining potency and selectivity relative to kinase targets. Neutral carboxylic acid replacements generally resulted in compounds that were significantly less potent and less selective relative to the charged species.